Morphological characteristics and phylogenetic analysis reveal a new species Punctulariopsis tenuis (Punctulariaceae, Basidiomycota) from southwestern China - Yuan, Qi; Li, Qi; Peng, Xiwen; Wang, Shunhong; Ma, Zhiqiang; Shu, Chengwei; Zhou, Yuelun; Zhao, Changlin (Charlie) (Phytotaxa, 2026)
Punctulariopsis is an important group of corticioid fungi, with only seven described species currently recognized. Recent studies have clarified the classification of Punctulariopsis by combing phylogenetic analyses and morphological evidence, but the species diversity of Punctulariopsis in the high-altitude forests of Yunnan Province, China, remains poorly explored. In this study, the detailed morphological observations and phylogenetic analyses based on the internal transcribed spacers (ITS) and the large subunit (LSU) of the nuclear ribosomal DNA (rDNA) revealed a new species in Punctulariopsis as P. tenuis sp. nov. This species is characterized by hard coriaceous basidiomata with smooth hymenial surface, a monomitic hyphal system and ellipsoid basidiospores measuring as 6.5–8.5 × 4.5–6.5 µm. The phylogenetical analysis revealed that the new species was nested within the genus Punctulariopsis in Punctulariaceae and showed that the new species constituted an independent lineage (100% BS, 1.00 BPP) closely related to P. asiana. A comprehensive description, micrograph, and phylogenetic analysis results are provided.